2017
DOI: 10.1002/cbin.10866
|View full text |Cite
|
Sign up to set email alerts
|

4‐Phenybutyric acid promotes gastric cancer cell migration via histone deacetylase inhibition‐mediated HER3/HER4 up‐regulation

Abstract: Dysregulation of histone acetylation plays an important role in tumor development. Histone acetylation regulates gene transcription and expression, which is reversibly regulated by histone acetyltransferase (HAT) and histone deacetylase (HDAC). As an HDAC inhibitor, 4-phenylbutyric acid (4-PBA) can increase histone acetylation levels by inhibiting HDAC activity. While 4-PBA inhibits proliferation of tumor cells in vitro, clinical trials have failed to show benefits of 4-PBA for refractory solid tumors. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Firstly, the 4-PBA treatment significantly promoted the cell migration in the following 24 h after scratch damage, indicating a stronger self-repairing capability of the IPEC-J2 monolayer enhanced by the 4-PBA. A previous study reported that 4-PBA promotes cell migration of MGC-803 and MGC-823 cell lines via histone deacetylase inhibition ( Shi et al., 2018 ). However, whether the 4-PBA exerts similar effects on histone deacetylase inhibition in the IPEC-J2 cells was unclear, which warrants continual study in our further work.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the 4-PBA treatment significantly promoted the cell migration in the following 24 h after scratch damage, indicating a stronger self-repairing capability of the IPEC-J2 monolayer enhanced by the 4-PBA. A previous study reported that 4-PBA promotes cell migration of MGC-803 and MGC-823 cell lines via histone deacetylase inhibition ( Shi et al., 2018 ). However, whether the 4-PBA exerts similar effects on histone deacetylase inhibition in the IPEC-J2 cells was unclear, which warrants continual study in our further work.…”
Section: Discussionmentioning
confidence: 99%
“…This protects EBV from acetylation by NAT1 during lytic replication. ERBB3 has been reported to be involved in mediating the regulations of acetylation and cell apoptosis through its signaling pathway [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein from cells and exosomes were detected by Western blot, performed as previously described (23). The target bands of proteins were detected with an enhanced chemiluminescence reagent (SuperSignal Western Pico Chemiluminescent Substrate, Pierce; Thermo Fisher Scientific, Inc.) and were scanned by the Electrophoresis Gel Imaging Analysis System (DNR Bio-Imaging Systems, Neve Yamin, Israel) and analyzed by NIH Image J software.…”
Section: Western Blotmentioning
confidence: 99%
“…The isolation of total RNA was performed as previously described (23). For microRNAs, The One Step PrimeScript R miRNA cDNA Synthesis Kit (Takara, Japan) was used for RNA reverse transcription.…”
Section: Rna Isolation and Reverse Transcription-quantitative Real-time Pcrmentioning
confidence: 99%